2024
DOI: 10.3390/stresses4010006
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Light on the Development of Lettuce and Cauliflower Seedlings

Adilson Antonio Rizzon,
Wendel Paulo Silvestre,
Camila Bonatto Vicenço
et al.

Abstract: The production of seedlings is one of the main activities for implementing agricultural crops. Many factors are involved in producing quality seedlings, including nutrition, health, genetics, and climatic factors such as temperature, humidity, and light. To evaluate the effect of light supplementation, a study was conducted using supplementary artificial light to produce lettuce and cauliflower seedlings. Sowing was carried out in styrofoam trays under a floating irrigation system. Part of the experiment conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Figure 4 shows the root and aerial parts of red cabbage and mustard seedlings grown under natural light (T1) and with purple LED light supplementation (T2). Red cabbage Rizzon et al [46], working with purple LED light supplementation (87.5 % red-670 nm + 12.5 % blue-430 nm) on curly lettuce and cauliflower seedlings in a greenhouse, observed that the biometric parameters of ADM, DRM, root length, and LA evaluated were positively influenced by light supplementation in both species. The same author commented that the use of lighting promoted the faster development of seedlings, indicating a shorter nursery time and, consequently, increased productivity compared to systems without supplementary lighting.…”
Section: Luminous Supplementation Of Mustard and Red Cabbage In A Gre...mentioning
confidence: 99%
“…Figure 4 shows the root and aerial parts of red cabbage and mustard seedlings grown under natural light (T1) and with purple LED light supplementation (T2). Red cabbage Rizzon et al [46], working with purple LED light supplementation (87.5 % red-670 nm + 12.5 % blue-430 nm) on curly lettuce and cauliflower seedlings in a greenhouse, observed that the biometric parameters of ADM, DRM, root length, and LA evaluated were positively influenced by light supplementation in both species. The same author commented that the use of lighting promoted the faster development of seedlings, indicating a shorter nursery time and, consequently, increased productivity compared to systems without supplementary lighting.…”
Section: Luminous Supplementation Of Mustard and Red Cabbage In A Gre...mentioning
confidence: 99%